PENGARUH BUDAYA KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA RS KARYA MEDIKA BANTAR GEBANG KOTA BEKASI - Saefulloh, Saefulloh (Jurnal Al-fatih Global Mulia, 2021)
The research objective is to analyze the relationship between work culture and leadership style on performance, both individually and collectively. The study was designed using a survey method with a correlational approach and the data obtained was analyzed statistically. The research was conducted at Karya Medika Bantar Gebang Hospital, Bekasi City, using a sample of 75 employees. Research data were collected by secondary data recording method and using a Likert-scale questionnaire that was calibrated using item validity tests and reliability coefficients. Analysis of the data using the correlation regression method, by first carrying out the requirements analysis test, namely the heteroscedasticity test and the estimated error normality test. The results of the study obtained a determinant coefficient value of 50.9%. This shows that the variable X_1 (Work Culture) X_2 (Leadership Style) influences the variable Y (Employee Performance) by 50.9% while the remaining 49.1% is influenced by other variables.